(untitled) (Journal of Health, Population and Nutrition, 2010)
An investigation was carried out during October 2005-September 2006 to determine the prevalence of bloodstream infections in patients attending the outpatient department of the HIV/AIDS clinic at the Lagos University Teaching Hospital in Nigeria. Two hundred and one patients-86 males and 115 females-aged 14-65 years were recruited for the study. Serological diagnosis was carried out on them to confirm their HIV status. Their CD4 counts were done using the micromagnetic bead method. Twenty mL of venous blood sample collected from each patient was inoculated into a pair of Oxoid Signal blood culture bottles for 2-14 days. Thereafter, 0.1 mL of the sample was plated in duplicates on MacConkey, blood and chocolate agar media and incubated at 37 °C for 18-24 hours. The CD4+ counts were generally low as 67% of 140 patients sampled had <200 cells/μL of blood. Twenty-six bacterial isolates were obtained from the blood samples and comprised 15 (58%) coagulase-negative staphylococci as follows: Staphylococcus epidermidis (7), S. cohnii cohnii (1), S. cohnii urealyticum (2), S. chromogenes (1), S. warneri (2), S. scuri (1), and S. xylosus (1). Others were 6 (23%) Gram-negative non-typhoid Salmonella spp., S. Typhimurium (4), S. Enteritidis (2); Pseudomonas fluorescens (1), Escherichia coli (1), Ochrobactrum anthropi (1), Moraxella sp. (1), and Chryseobacterium meningosepticum. Results of antimicrobial susceptibility tests showed that coagulase-negative staphylococci had good sensitivities to vancomycin and most other antibiotics screened but were resistant mainly to ampicilin and tetracycline. The Gram-negative organisms isolated also showed resistance to ampicillin, tetracycline, chloramphenicol, and septrin. This study demonstrates that co-agulase-negative staphylococci and non-typhoidal Salmonellae are the most common aetiological agents of bacteraemia among HIV-infected adults attending the Lagos University Teaching Hospital, Nigeria. The organisms were resistant to oldergeneration antibiotics often prescribed in this environment but were sensitive to vancomycin, cefotaxime, cefuroxime, and other new-generation antibiotics. Key words: Bacteraemia; Bacterial infections; HIV; HIV infections; Nigeria DOI: 10.3329/jhpn.v28i4.6037 J HEALTH POPUL NUTR 2010 Aug;28(4):318-326